Unsaturated phospholipid modified FeOCl nanosheets for enhancing tumor ferroptosis. Issue 9 (6th February 2023) - He, Zi; Guo, Yijun; Chen, Jinzhu; Luo, Huiling; Liu, Xinxin; Zhang, Xiuming; Sun, Yanan; Ge, Dongtao; Ye, Shefang; Shi, Wei
Abstract : The unsaturated phospholipid and polyacrylic acid functionalized FeOCl nanosheets achieved the amplification of lipid peroxides, and enhanced tumor ferroptosis. Abstract : Iron-dependent accumulation of reactive oxygen species (ROS) and lipid peroxidation play key roles in ferroptosis, which has been an attractive strategy to kill tumor cells. However, the rapid annihilation of hydroxyl radicals (˙OH) produced from the Fenton reaction has become a major obstacle in inducing lipid peroxidation in cells. In this study, we develop a nano-delivery system of unsaturated phospholipid (Lip) and polyacrylic acid (PAA) functionalized FeOCl nanosheets (FeOCl@PAA-Lip). In this system, the ˙OH radicals produced from the Fenton reaction between FeOCl nanosheets and endogenous H2 O2 of tumor cells attack Lip on the nanosheets in situ to initiate the lipid peroxidation chain reaction, which not only realizes free radical conversion but also leads to the amplification of ROS and lipid peroxides, thus enhancing tumor ferroptosis. The in vitro and in vivo results confirmed that FeOCl@PAA-Lip nanosheets exhibited specific tumor cell-killing effects, good biocompatibility, long circulation time, low side effects, high tumor targeting and an excellent tumor inhibition rate (73%). The Lip functionalization strategy offers a paradigm of enhancing ferroptosis treatment by conversion of ˙OH/phospholipid radicals/lipid peroxyl radicals and strengthening lipid peroxidation.